Oxygen-containing whitening toothpaste and preparation method thereof

By using a vanillin-based silica-type crosslinking agent to crosslink chitosan, a chitosan-urea peroxide gel is formed, which solves the problems of poor compatibility and insufficient stability of urea peroxide in toothpaste, thus improving the stability and safety of whitening toothpaste.

CN121003566AInactive Publication Date: 2025-11-25GUANGDONG HUAJIAN BIOLOGICAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511173396.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-21
Publication Date
2025-11-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing toothpastes contain urea peroxide, which has poor compatibility with other ingredients and insufficient stability, resulting in poor whitening effects and potential safety hazards.

Method used

Chitosan was cross-linked with a vanillin-based silica-type cross-linking agent to form a chitosan-urea peroxide gel, which was then coated with urea peroxide to prepare an oxygen-containing whitening toothpaste.

Benefits of technology

It improves the compatibility of urea peroxide with other ingredients in toothpaste, enhances the chemical stability of urea peroxide, and ensures the whitening effect and safety of toothpaste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
  • Figure SMS_5
    Figure SMS_5
Patent Text Reader

Abstract

The invention relates to the technical field of whitening toothpaste, and discloses oxygen-containing whitening toothpaste and a preparation method thereof.The preparation method of the oxygen-containing whitening toothpaste comprises the steps that on the basis of a free radical polymerization reaction mechanism, an alkenyl vanillin-based monomer and alkenyl silicon dioxide particles serve as raw materials, and a vanillin-based silicon dioxide type cross-linking agent is prepared; the preparation method comprises the following steps: cross-linking chitosan by using a vanillin-based silicon dioxide type cross-linking agent, and coating solid urea peroxide by using a formed gel carrier, so as to prepare chitosan-urea peroxide gel; chitosan-urea peroxide gel is used as a functional component and is mixed with basic raw materials in the toothpaste, and then the oxygen-containing whitening toothpaste is prepared through a vacuum homogenization process. The oxygen-containing whitening toothpaste prepared by the invention has a good whitening effect and can be used for improving the color and luster of teeth.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of whitening toothpaste technology, and more particularly to an oxygen-containing whitening toothpaste and its preparation method. Background Technology

[0002] With societal progress and rising living standards, traditional toothpaste alone can no longer meet people's daily oral hygiene needs. This has led to the development of functional toothpastes with whitening, anti-sensitivity, and antibacterial / anti-inflammatory properties. As people become more aware of dental health and aesthetics, the demand for teeth whitening is growing rapidly, with more consumers focusing on whitening, making whitening toothpaste one of the steadily developing categories in the toothpaste industry.

[0003] Teeth are important functional organs of the human body. Normal teeth are a glossy, translucent ivory color. Tooth discoloration and yellowing are mainly caused by intrinsic or extrinsic staining. Intrinsic staining refers to the color change of teeth caused by pigments deposited inside the teeth due to various factors, such as medications and dental diseases. Extrinsic staining is caused by sticky substances secreted by bacteria on the tooth surface, which bind food debris, sugars, bacteria, proteins, etc. Pigments from daily diets such as tea, coffee, and tobacco adhere to these sticky substances, gradually causing teeth to turn yellow or black.

[0004] Adding whitening active ingredients such as peroxides (e.g., hydrogen peroxide, urea peroxide) to toothpaste allows the release of active oxygen, which reacts with pigments on the enamel surface to remove stains and pigment deposits, thus achieving a whitening effect. Furthermore, brushing allows the active oxygen to penetrate into the micropores of the enamel, further enhancing the whitening effect.

[0005] Studies have found that solid urea peroxide, compared to other peroxides, has advantages such as high reactive oxygen species (ROS) value, high solubility, and relatively stable chemical properties, making it a preferred ingredient in peroxide-based whitening toothpastes. However, urea peroxide is not well-compatible with some commonly used ingredients in toothpaste formulations. These ingredients can accelerate the oxidation of urea peroxide itself, especially since moisture in toothpaste can more easily promote the oxidation reaction, releasing ROS and thus diminishing its whitening effect on teeth. This can also lead to toothpaste swelling and make it difficult for urea peroxide to maintain long-term stability. Summary of the Invention

[0006] This invention utilizes a self-developed vanillin-based silica crosslinking agent to crosslink chitosan, forming a gel carrier with encapsulation capabilities, to encapsulate solid urea peroxide, thus preparing a chitosan-urea peroxide gel. This gel is then compounded with other basic raw materials to prepare an oxygen-containing toothpaste with whitening effects.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: a method for preparing an oxygen-containing whitening toothpaste, comprising the following steps: Step 1: Based on the free radical polymerization mechanism, a vanillin-based silica crosslinking agent was prepared using alkenylated vanillin monomer and alkenylated silica particles as raw materials. The chemical structure of the alkenylated vanillin monomer is as follows: ; Step 2: Crosslink chitosan with vanillin-based silica crosslinking agent to form a gel carrier that coats solid urea peroxide, thus preparing chitosan-urea peroxide gel; Step 3: Using chitosan-urea peroxide gel as a functional component, mix it with the basic raw materials in the toothpaste, and then prepare oxygen-containing whitening toothpaste through a vacuum homogenization process.

[0008] Furthermore, the preparation method of the alkenylated vanillin monomer is as follows: Based on the carboxyl-hydroxy esterification reaction mechanism, N-(tert-butyloxycarbonyl)glycine reacts with hydroxyethyl methacrylate in a 1:1 molar ratio under the catalysis of protic acid, and then the protective tert-butyloxycarbonyl group is removed to prepare an alkenylated glycine monomer. Based on the amino-epoxy ring-opening reaction mechanism, alkenylated glycine monomers react with epichlorohydrin in a 1:1 molar ratio to prepare alkenylated glycine monomers with chlorine functional groups. Based on the substitution reaction mechanism, an alkenylated glycine monomer with chlorine functional groups reacts with vanillin in a 1:1 molar ratio to prepare an alkenylated vanillin monomer.

[0009] Furthermore, the protic acid is either trifluoromethanesulfonic acid or p-toluenesulfonic acid.

[0010] Furthermore, the method for preparing the alkenylated silica particles is as follows: hydroxylation of the silica particle surface is performed using an aqueous hydrogen peroxide solution to obtain hydroxylated silica particles; Alkenylated silica particles were prepared by modifying hydroxylated silica particles with vinyltriethoxysilane.

[0011] Furthermore, the average particle size of the silica particles is 10 μm.

[0012] Furthermore, the mass ratio of the alkenylated silica particles to the alkenylated vanillin monomer is 1:0.5-1.

[0013] Furthermore, the content of the vanillin-based silica crosslinking agent is 1-5 wt% of the amount of chitosan used.

[0014] Furthermore, the preparation method of the chitosan-urea peroxide gel is as follows: dissolving chitosan in an acetic acid solution to obtain a chitosan-acetic acid solution; Urea peroxide was added to the prepared chitosan acetate solution, mixed well, and then a vanillin-based silica crosslinking agent was added to carry out a crosslinking reaction for 20-30 minutes to prepare chitosan-urea peroxide gel.

[0015] Furthermore, the acetic acid solution has a mass fraction of 1-5%.

[0016] Furthermore, the formula for the whitening toothpaste is as follows: 20-30 parts by weight of sorbitol; 0.6-0.9 parts by weight of carbomer; 0.2-0.4 parts by weight of xanthan gum; 4-6 parts by weight of polyethylene glycol; 3-10 parts by weight of chitosan-urea peroxide gel; 0.1-0.3 parts by weight of sodium saccharin; 0.5-1.5 parts by weight of peppermint powder flavoring 0.5-1.5 parts by weight of sodium lauryl sulfate; 0.7-0.9 parts by weight of sodium benzoate; 25-75 parts by weight of deionized water.

[0017] The beneficial effects of this invention are as follows: This invention designs and synthesizes a novel alkenyl vanillin monomer. Based on the free radical polymerization mechanism, using safe and environmentally friendly alkenyl vanillin monomer and alkenyl silica particles with good whitening effect as raw materials, a vanillin silica crosslinking agent is prepared. Subsequently, chitosan was cross-linked using a vanillin-based silica cross-linking agent, and the resulting gel carrier coated solid urea peroxide to prepare chitosan-urea peroxide gel. Finally, using chitosan-urea peroxide gel as a functional component, it was mixed with other basic raw materials in the toothpaste and homogenized under vacuum to prepare oxygen-containing whitening toothpaste; Experimental results demonstrate that the oxygen-containing whitening toothpaste prepared according to this invention has a good whitening effect. Detailed Implementation

[0018] To address the issues of poor compatibility and insufficient stability of urea peroxide in toothpaste, as well as the cytotoxicity of the traditional cross-linking agent glutaraldehyde, this invention independently developed a vanillin-based silica-type cross-linking agent. This agent is used to cross-link chitosan to form a gel and encapsulate urea peroxide. This not only improves the compatibility of urea peroxide with other raw materials in toothpaste but also enhances the chemical stability of urea peroxide. Moreover, the raw materials are safe and reliable.

[0019] Example 1: The preparation of a vanillin-based silica-type crosslinking agent includes the following steps: (1) Preparation of alkenylated glycine monomer. The preparation mechanism is as follows: under the catalysis of p-toluenesulfonic acid catalyst, the carboxyl group in N-(tert-butyloxycarbonyl)glycine reacts with the hydroxyl group in hydroxyethyl methacrylate, and then the protective tert-butyloxycarbonyl (boc group) is removed to prepare alkenylated glycine monomer. The specific experimental steps are as follows: under nitrogen protection, 3g of N-(tert-butyloxycarbonyl)glycine and 2.3g of hydroxyethyl methacrylate are added to 50mL of N,N-dimethylformamide, mechanically stirred evenly, p-toluenesulfonic acid is added, mixed, the temperature is raised to 110℃, and the reaction is stirred for 8h. After the reaction is completed, it is naturally cooled, the solvent is removed by vacuum distillation, filtered, washed, and vacuum dried at 60℃ for 10h to prepare alkenylated N-(tert-butyloxycarbonyl)glycine. 4g of alkenylated N-(tert-butoxycarbonyl)glycine was dissolved in 80mL of dichloromethane, and 7.8g of trifluoroacetic acid was added. After the addition was complete, the mixture was stirred at room temperature for 3h. After the reaction was complete, the solvent was removed by rotary evaporation, and the mixture was recrystallized once with dichloromethane to prepare the alkenylated glycine monomer. (2) Preparation of chlorine-functionalized alkenyl glycine monomer. The preparation mechanism is as follows: the amino group in the alkenyl glycine monomer reacts with the epoxy group in epichlorohydrin to open the ring, and the chlorine-functionalized alkenyl glycine monomer is prepared. The specific experimental steps are as follows: 3g of alkenyl glycine monomer is mixed with 30mL of deionized water and mechanically stirred until it is evenly dissolved to obtain an aqueous solution of alkenyl glycine monomer. 1.5g of epichlorohydrin and 15mL of deionized water are added to a 250mL four-necked round-bottom flask equipped with a dropping funnel, thermometer, condenser and magnetic stirrer. The mixture is stirred and heated to 50℃. Then the obtained alkenyl glycine monomer aqueous solution is added dropwise for 1h. After the addition is completed, the temperature is raised to 55℃ and the reaction is kept at 2h. After the reaction is completed, the mixture is cooled to room temperature, the solid product is filtered out and placed in a vacuum drying oven at 60℃ for 8h to prepare the chlorine-functionalized alkenyl glycine monomer. (3) Preparation of alkenyl vanillin monomer. The preparation mechanism is as follows: Under the catalysis of sodium hydroxide, the chlorine functional group in the alkenyl glycine monomer with chlorine functional group undergoes a nucleophilic substitution reaction with the phenolic hydroxyl functional group in vanillin to prepare the alkenyl vanillin monomer. The specific experimental steps are as follows: 5.6g of alkenyl glycine monomer with chlorine functional group is dispersed in 50mL of deionized water to obtain a solution of alkenyl glycine monomer with chlorine functional group. 0.8g of sodium hydroxide and 50mL of deionized water are then added to the solution. Water was added to a 250 mL three-necked flask, stirred, and cooled to room temperature. Then, 3.1 g of vanillin was added under nitrogen and reflux conditions. The mixture was stirred mechanically at 80 °C for 1 h to form a salt solution. The obtained chlorine-functionalized alkenylated glycine monomer solution was then added dropwise to the three-necked flask over 1 h. After the addition was complete, the system temperature was raised to 100 °C and stirred for 4 h. After cooling to room temperature, the mixture was recrystallized, filtered, and dried under vacuum at 50 °C for 8 h to prepare the alkenylated vanillin monomer. The chemical structural formula of the alkenylated vanillin monomer is: ; The 1H NMR characterization of the alkenyl vanillin monomer is as follows: 1 H NMR (DMSO-d6, 400MHz) δ: 1.92 (s, 3H), 2.80-2.92 (m, 2H), 3.39-3.47 (m, 2H), 3.86 (s, 3H), 3.95-3.96 (d, 2H), 3.99-4.04 (m, 1H), 4.33- 4.42(m, 4H), 4.56-4.57(d, 1H), 4.68-4.73(m, 1H), 5.72-5.81(d, 2H), 7.05-7.07(d, 1H), 7.40(s, 1H), 7.50-7.52(d, 1H), 9.85(s, 1H); (4) Preparation of alkenylated silica particles. The preparation mechanism is as follows: silica particles are modified with vinyltriethoxysilane to prepare alkenylated silica particles. The specific experimental steps are as follows: 5g silica particles (average particle size of 10μm) and 50mL hydrogen peroxide aqueous solution (30wt%) are added to the reactor, ultrasonically dispersed for 20min, the system temperature is raised to 105℃ under stirring, refluxed for 4h, cooled to room temperature, centrifuged, washed, and finally vacuum dried at 80℃ for 6h to prepare hydroxylated silica particles. 6g of hydroxylated silica particles and 4mL of vinyltriethoxysilane were added to 150mL of toluene. The magnetic stirrer was turned on and the mixture was refluxed for 24h. Then 30mL of deionized water was added and the mixture was continuously refluxed and stirred for 24h. The mixture was filtered, washed, and dried in a vacuum drying oven at 80℃ for 5h to prepare alkenylated silica particles. (5) Preparation of vanillin-based silica crosslinking agent. The preparation mechanism is as follows: Based on the free radical polymerization reaction mechanism, vanillin-based silica crosslinking agent is prepared by using alkenylated vanillin monomer and alkenylated silica particles as raw materials. The specific experimental steps are as follows: 2g of alkenylated silica particles and 1.6g of alkenylated vanillin monomer are added to 50mL of N-methylpyrrolidone. After mechanical stirring for 10min, the temperature is raised to 60℃, 0.04g of initiator azobisisobutyronitrile is added, and the reaction is continued to be stirred for 24h. After the reaction is completed, the mixture is cooled to room temperature, centrifuged to obtain solid, and dried at 80℃ for 12h to prepare vanillin-based silica crosslinking agent.

[0020] Example 2: The preparation of chitosan-urea peroxide gel includes the following steps: 3g of chitosan (average molecular weight 3×10) 5 Chitosan acetate solution was prepared by dissolving chitosan (with a degree of deacetylation of 80%-90%) in 50 mL of 2% acetic acid solution. 6g of urea peroxide was added to the prepared chitosan acetate solution, mixed well, and 0.05g of vanillin-based silica crosslinking agent was added to carry out the crosslinking reaction for 25 minutes to prepare chitosan-urea peroxide gel.

[0021] Example 3: An oxygen-containing whitening toothpaste, formula a, has the following ingredients: Sorbitol, 25 parts by weight; Carbomer 940, 0.7 parts by weight; Xanthan gum, 0.3 parts by weight; Polyethylene glycol-400, 5 parts by weight; Chitosan-urea peroxide gel, 6 parts by weight; Sodium saccharin, 0.2 parts by weight; Peppermint powder flavoring, 1 part by weight; Sodium lauryl sulfate, 1 part by weight; Sodium benzoate, 0.8 parts by weight; Deionized water, 60 parts by weight; The preparation method of oxygen-containing whitening toothpaste A includes the following steps: Step 1: Mix carbomer 940, xanthan gum, sodium lauryl sulfate, and chitosan-urea peroxide gel, stir well, and obtain material one; Step 2: Dissolve sodium benzoate and sodium saccharin in deionized water, then add sorbitol and polyethylene glycol-400 to obtain material 2; Step 3: Add material 1 to material 2, vacuum homogenize for 30 minutes, open the lid and add peppermint powder flavoring, vacuum homogenize for 15 minutes, vacuum degas for 5 minutes, and prepare oxygen-containing whitening toothpaste a; Performance testing: I. Quality Evaluation (1) Appearance test: Observe the gloss, fineness, stringing phenomenon and presence of foreign matter of the oxygen whitening toothpaste a prepared in this invention; The appearance test results are as follows: glossy color, fine texture, uniform and free of foreign matter; (2) Strip formation test: Using the oxygen-containing whitening toothpaste a prepared in this invention as a sample, 2 cm of sample was squeezed out from the toothpaste tube with a diameter of 6 mm and placed on the toothbrush. The shape retention of the sample on the toothbrush was observed for 10 min. The strip-forming test results are as follows: the sample basically retains its original shape after 10 minutes on the toothbrush, indicating that the oxygen-containing whitening toothpaste a prepared in this invention has good strip-forming properties; (3) Stability and hard particle test: The oxygen whitening toothpaste a prepared in this invention was tested for stability and hard particles according to GB / T 8372-2017 "Toothpaste"; The stability test results are as follows: Oxygen whitening toothpaste a was placed in a refrigerator at -8℃ for 8 hours, and then in a constant temperature incubator at 45℃ for 8 hours. After being taken out and brought to room temperature, the toothpaste did not overflow from the tube. When the toothpaste tube was inverted, no liquid dripped from the tube within 10 seconds. After the toothpaste was squeezed out, its aroma and color were normal compared with the toothpaste sample stored at room temperature. The test results for hard particles showed that the glass slide had no scratches. (4) pH value determination: Weigh 5g of oxygen whitening toothpaste a and place it in a 50mL beaker. Add 20mL of boiled and cooled distilled water, stir well, and use a pH meter to determine the pH value at 20℃. The pH value test results are as follows: The pH value of the oxygen-containing whitening toothpaste a prepared in this invention is 6.45; (5) Foaming property test: Place 5g of oxygen whitening toothpaste a in a 50mL beaker, add 15mL of deionized water, disperse beforehand, and then stir on a magnetic stirrer at a speed of 1500r / min for 2min. Record the maximum foam amount and foam stability. The maximum foam amount = foam height after stirring for 2min, and the foam stability = foam height after standing for 30min / foam height after stirring for 2min. The foaming test results were as follows: maximum foam volume was 1.93 mm, and foam stability was 0.81. II. Whitening effect test: (1) 80 subjects were recruited. The inclusion criteria for subjects were as follows: Healthy adults aged 20-55; Consumers who want to improve the color of their teeth (such as yellow teeth, stains on the surface of teeth, etc.); I have not received any professional teeth whitening treatment in the past six months; Good oral health, with no serious periodontal disease or dental disease; (2) 80 subjects were randomly divided into 4 groups of 20 people each, with half male and half female. The subjects were given oxygen whitening toothpaste a and toothbrush and brushed their teeth once in the morning and once in the evening, for a total of 2 times, each time for 1 minute. (3) Before use, the subject’s pigmentation index was tested (baseline). After 100 days of continuous use, the pigmentation index was tested again. The changes in the pigmentation index of the subject before and after using oxygen whitening toothpaste a were compared. The pigmentation index scoring rules are shown in Table 1. Table 1. Scoring Rules for Pigmentation Index The teeth examined were the labial and lingual surfaces of the mandibular anterior teeth and the labial surface of the maxillary anterior teeth. The stain index for each tooth surface was calculated as the product of the stain area score and the stain severity score. The stain index score for each subject was the average of the stain index scores for each tooth surface, i.e.: stain index = ∑(area score, severity score) / total number of tooth surfaces examined; Teeth whitening effect was evaluated based on changes in the tooth stain index. The baseline stain index, the stain index after 100 days of use, and the stain index reduction rate were measured for each experimental group. The stain index reduction rate was calculated as follows: (average stain index before use - average stain index after use) / average stain index before use × 100%. The test results are shown in Table 2 below; Table 2 Results of Pigmentation Index Measurement III. Sensitivity Test: A questionnaire survey was conducted on 80 participants who participated in the whitening effect test to determine whether they experienced symptoms such as swollen and red gums, irritation when exposed to cold, heat, acid, or sweetness, or ulcers after using oxygen whitening toothpaste a. The sensitivity test results showed that none of the 80 subjects experienced symptoms such as swollen and red gums, irritation from hot, cold, sour, or sweet foods, or ulcers.

[0022] Example 4: An oxygen-containing whitening toothpaste, b, has the following ingredient formula: Sorbitol, 25 parts by weight; Carbomer 940, 0.7 parts by weight; Xanthan gum, 0.3 parts by weight; Polyethylene glycol-400, 5 parts by weight; Chitosan-urea peroxide gel, 3 parts by weight; Sodium saccharin, 0.2 parts by weight; Peppermint powder flavoring, 1 part by weight; Sodium lauryl sulfate, 1 part by weight; Sodium benzoate, 0.8 parts by weight; Deionized water, 63 parts by weight; The preparation method of oxygen-containing whitening toothpaste b includes the following steps: Step 1: Mix carbomer 940, xanthan gum, sodium lauryl sulfate, and chitosan-urea peroxide gel, stir well, and obtain material one; Step 2: Dissolve sodium benzoate and sodium saccharin in deionized water, then add sorbitol and polyethylene glycol-400 to obtain material 2; Step 3: Add material 1 to material 2, vacuum homogenize for 30 minutes, open the lid and add peppermint powder flavoring, vacuum homogenize for 15 minutes, vacuum degas for 5 minutes, and prepare oxygen-containing whitening toothpaste b. Performance testing: I. Quality Evaluation (1) Appearance test: Observe the gloss, fineness, stringing phenomenon and presence of foreign matter of the oxygen whitening toothpaste b prepared in this invention; The appearance test results are as follows: glossy color, fine texture, uniform and free of foreign matter; (2) Strip formation test: Using the oxygen-containing whitening toothpaste b prepared in this invention as a sample, 2 cm of sample was squeezed out from the toothpaste tube with a diameter of 6 mm and placed on the toothbrush. The shape retention of the sample on the toothbrush was observed for 10 min. The strip formation test results are as follows: the sample basically retains its original shape after 10 minutes on the toothbrush, indicating that the oxygen-containing whitening toothpaste b prepared in this invention has good strip formation properties; (3) Stability and hard particle test: The stability and hard particle test of the oxygen whitening toothpaste b prepared in this invention were carried out according to GB / T 8372-2017 "Toothpaste"; The stability test results are as follows: Oxygen whitening toothpaste b was placed in a refrigerator at -8℃ for 8 hours, and then in a constant temperature incubator at 45℃ for 8 hours. After being taken out and restored to room temperature, the toothpaste did not overflow from the tube. When the toothpaste tube was inverted, no liquid dripped from the tube within 10 seconds. After the toothpaste was squeezed out, its aroma and color were normal compared with the toothpaste sample stored at room temperature. The test results for hard particles showed that the glass slide had no scratches. (4) pH value determination: Weigh 5g of oxygen whitening toothpaste b and place it in a 50mL beaker. Add 20mL of boiled and cooled distilled water, stir well, and use a pH meter to measure the pH value at 20℃. The pH value test results are as follows: The pH value of the oxygen-containing whitening toothpaste b prepared in this invention is 6.45; (5) Foaming property test: Place 5g of oxygen whitening toothpaste b in a 50mL beaker, add 15mL of deionized water, disperse beforehand, and then stir on a magnetic stirrer at a speed of 1500r / min for 2min. Record the maximum foam amount and foam stability. The maximum foam amount = foam height after stirring for 2min, and the foam stability = foam height after standing for 30min / foam height after stirring for 2min. The foaming test results were as follows: maximum foam volume was 1.93 mm, and foam stability was 0.81. II. Whitening effect test: (1) 80 subjects were recruited. The inclusion criteria for subjects were as follows: Healthy adults aged 20-55; Consumers who want to improve the color of their teeth (such as yellow teeth, stains on the surface of teeth, etc.); I have not received any professional teeth whitening treatment in the past six months; Good oral health, with no serious periodontal disease or dental disease; (2) 80 subjects were randomly divided into 4 groups of 20 people each, with half male and half female. All subjects were given oxygen whitening toothpaste b and toothbrushes. They brushed their teeth once in the morning and once in the evening, for a total of 2 times, for 1 minute each time, according to the Bass brushing method. (3) Before use, the subject’s pigmentation index was tested (baseline). After 100 days of continuous use, the pigmentation index was tested again to compare the changes in the pigmentation index of the subject before and after using oxygen whitening toothpaste b. The pigmentation index scoring rules are shown in Table 3. Table 3. Scoring Rules for Pigmentation Index The teeth examined were the labial and lingual surfaces of the mandibular anterior teeth and the labial surface of the maxillary anterior teeth. The stain index for each tooth surface was calculated as the product of the stain area score and the stain severity score. The stain index score for each subject was the average of the stain index scores for each tooth surface, i.e.: stain index = ∑(area score, severity score) / total number of tooth surfaces examined; Teeth whitening effect was evaluated based on changes in the tooth stain index. The baseline stain index, the stain index after 100 days of use, and the stain index reduction rate were measured for each experimental group. The stain index reduction rate was calculated as follows: (average stain index before use - average stain index after use) / average stain index before use × 100%. The test results are shown in Table 4 below; Table 4 Results of Pigmentation Index Measurement III. Sensitivity Test: A questionnaire survey was conducted on 80 participants who participated in the whitening effect test to determine whether they experienced symptoms such as swollen and red gums, irritation when exposed to cold, heat, acid, or sweetness, or ulcers after using oxygen whitening toothpaste b. The sensitivity test results showed that none of the 80 subjects experienced symptoms such as swollen and red gums, irritation from hot, cold, sour, or sweet foods, or ulcers.

[0023] Example 5: An oxygen-containing whitening toothpaste, c, has the following ingredient formula: Sorbitol, 25 parts by weight; Carbomer 940, 0.7 parts by weight; Xanthan gum, 0.3 parts by weight; Polyethylene glycol-400, 5 parts by weight; Chitosan-urea peroxide gel, 10 parts by weight; Sodium saccharin, 0.2 parts by weight; Peppermint powder flavoring, 1 part by weight; Sodium lauryl sulfate, 1 part by weight; Sodium benzoate, 0.8 parts by weight; Deionized water, 56 parts by weight; The preparation method of oxygen-containing whitening toothpaste c includes the following steps: Step 1: Mix carbomer 940, xanthan gum, sodium lauryl sulfate, and chitosan-urea peroxide gel, stir well, and obtain material one; Step 2: Dissolve sodium benzoate and sodium saccharin in deionized water, then add sorbitol and polyethylene glycol-400 to obtain material 2; Step 3: Add material 1 to material 2, vacuum homogenize for 30 minutes, open the lid and add peppermint powder flavoring, vacuum homogenize for 15 minutes, vacuum degas for 5 minutes, and prepare oxygen-containing whitening toothpaste c; Performance testing: I. Quality Evaluation (1) Appearance test: Observe the gloss, fineness, stringing phenomenon and presence of foreign matter of the oxygen whitening toothpaste c prepared in this invention; The appearance test results are as follows: glossy color, fine texture, uniform and free of foreign matter; (2) Strip formation test: Using the oxygen whitening toothpaste c prepared in this invention as a sample, 2 cm of sample was squeezed out from the toothpaste tube with a diameter of 6 mm and placed on the toothbrush. The shape retention of the sample on the toothbrush was observed for 10 min. The strip formation test results are as follows: the sample basically retains its original shape after 10 minutes on the toothbrush, indicating that the oxygen-containing whitening toothpaste prepared in this invention has good strip formation properties. (3) Stability and hard particle test: The oxygen whitening toothpaste c prepared in this invention was tested for stability and hard particles according to GB / T 8372-2017 "Toothpaste"; The stability test results were as follows: Oxygen whitening toothpaste c was placed in a refrigerator at -8℃ for 8 hours, and then in a constant temperature incubator at 45℃ for 8 hours. After being taken out and brought to room temperature, the toothpaste did not overflow from the tube. When the toothpaste tube was inverted, no liquid dripped from the tube within 10 seconds. After the toothpaste was squeezed out, its aroma and color were normal compared with the toothpaste sample stored at room temperature. The test results for hard particles showed that the glass slide had no scratches. (4) pH value determination: Weigh 5g of oxygen whitening toothpaste c and place it in a 50mL beaker. Add 20mL of boiled and cooled distilled water, stir well, and use a pH meter to measure the pH value at 20℃. The pH value test results are as follows: The pH value of the oxygen-containing whitening toothpaste c prepared in this invention is 6.45; (5) Foaming property test: Place 5g of oxygen whitening toothpaste c in a 50mL beaker, add 15mL of deionized water, disperse beforehand, and then stir on a magnetic stirrer at a speed of 1500r / min for 2min. Record the maximum foam amount and foam stability. The maximum foam amount = foam height after stirring for 2min, and the foam stability = foam height after standing for 30min / foam height after stirring for 2min. The foaming test results were as follows: maximum foam volume was 1.93 mm, and foam stability was 0.81. II. Whitening effect test: (1) 80 subjects were recruited. The inclusion criteria for subjects were as follows: Healthy adults aged 20-55; Consumers who want to improve the color of their teeth (such as yellow teeth, stains on the surface of teeth, etc.); I have not received any professional teeth whitening treatment in the past six months; Good oral health, with no serious periodontal disease or dental disease; (2) 80 subjects were randomly divided into 4 groups of 20 people each, with half males and half females. All subjects were given oxygen whitening toothpaste and toothbrushes. They brushed their teeth once in the morning and once in the evening, for a total of 2 times, for 1 minute each time, according to the Bass brushing method. (3) Before use, the subject’s pigmentation index was tested (baseline). After 100 days of continuous use, the pigmentation index was tested again. The changes in the pigmentation index of the subject before and after using oxygen whitening toothpaste c were compared. The pigmentation index scoring rules are shown in Table 5. Table 5. Scoring Rules for the Pigmentation Index The teeth examined were the labial and lingual surfaces of the mandibular anterior teeth and the labial surface of the maxillary anterior teeth. The stain index for each tooth surface was calculated as the product of the stain area score and the stain severity score. The stain index score for each subject was the average of the stain index scores for each tooth surface, i.e.: stain index = ∑(area score, severity score) / total number of tooth surfaces examined; Teeth whitening effect was evaluated based on changes in the tooth stain index. The baseline stain index, the stain index after 100 days of use, and the stain index reduction rate were measured for each experimental group. The stain index reduction rate was calculated as follows: (average stain index before use - average stain index after use) / average stain index before use × 100%. The test results are shown in Table 6 below; Table 6 Results of Pigmentation Index Measurement III. Sensitivity Test: A questionnaire survey was conducted on 80 participants who participated in the whitening effect test to determine whether they experienced symptoms such as swollen and red gums, irritation when exposed to cold, heat, acid, or sweetness, or ulcers after using oxygen whitening toothpaste. The sensitivity test results showed that none of the 80 subjects experienced symptoms such as swollen and red gums, irritation from hot, cold, sour, or sweet foods, or ulcers.

Claims

1. A method for preparing an oxygen-containing whitening toothpaste, characterized in that, Includes the following steps: Step 1: Based on the free radical polymerization mechanism, a vanillin-based silica crosslinking agent was prepared using alkenylated vanillin monomer and alkenylated silica particles as raw materials. The chemical structure of the alkenylated vanillin monomer is as follows: ; Step 2: Crosslink chitosan with vanillin-based silica crosslinking agent to form a gel carrier that coats solid urea peroxide, thus preparing chitosan-urea peroxide gel; Step 3: Using chitosan-urea peroxide gel as a functional component, mix it with the basic raw materials in the toothpaste, and then prepare oxygen-containing whitening toothpaste through a vacuum homogenization process.

2. The method for preparing an oxygen-containing whitening toothpaste according to claim 1, characterized in that, The preparation method of the alkenylated vanillin monomer is as follows: Based on the carboxyl-hydroxy esterification reaction mechanism, N-(tert-butyloxycarbonyl)glycine reacts with hydroxyethyl methacrylate in a 1:1 molar ratio under the catalysis of protic acid, and then the protective tert-butyloxycarbonyl group is removed to prepare an alkenylated glycine monomer. Based on the amino-epoxy ring-opening reaction mechanism, alkenylated glycine monomers react with epichlorohydrin in a 1:1 molar ratio to prepare alkenylated glycine monomers with chlorine functional groups. Based on the substitution reaction mechanism, an alkenylated glycine monomer with chlorine functional groups reacts with vanillin in a 1:1 molar ratio to prepare an alkenylated vanillin monomer.

3. The method for preparing an oxygen-containing whitening toothpaste according to claim 2, characterized in that, The protic acid is either trifluoromethanesulfonic acid or p-toluenesulfonic acid.

4. The method for preparing an oxygen-containing whitening toothpaste according to claim 1, characterized in that, The method for preparing the alkenylated silica particles is as follows: hydroxylation of the surface of silica particles is performed using an aqueous hydrogen peroxide solution to obtain hydroxylated silica particles; Alkenylated silica particles were prepared by modifying hydroxylated silica particles with vinyltriethoxysilane.

5. The method for preparing an oxygen-containing whitening toothpaste according to claim 4, characterized in that, The average particle size of the silica particles is 10 μm.

6. The method for preparing an oxygen-containing whitening toothpaste according to claim 1, characterized in that, The mass ratio of the alkenylated silica particles to the alkenylated vanillin monomer is 1:0.5-1.

7. The method for preparing an oxygen-containing whitening toothpaste according to claim 1, characterized in that, The content of the vanillin-based silica crosslinking agent is 1-5 wt% of the amount of chitosan.

8. The method for preparing an oxygen-containing whitening toothpaste according to claim 1, characterized in that, The preparation method of the chitosan-urea peroxide gel is as follows: dissolve chitosan in an acetic acid solution to obtain a chitosan acetic acid solution; Urea peroxide was added to the prepared chitosan acetate solution, mixed well, and then a vanillin-based silica crosslinking agent was added to carry out a crosslinking reaction for 20-30 minutes to prepare chitosan-urea peroxide gel.

9. The method for preparing an oxygen-containing whitening toothpaste according to claim 8, characterized in that, The acetic acid solution has a mass fraction of 1-5%.

10. An oxygen-containing whitening toothpaste prepared according to any one of claims 1-9, characterized in that, The formula for the whitening toothpaste is as follows: 20-30 parts by weight of sorbitol; 0.6-0.9 parts by weight of carbomer; 0.2-0.4 parts by weight of xanthan gum; 4-6 parts by weight of polyethylene glycol; 3-10 parts by weight of chitosan-urea peroxide gel; 0.1-0.3 parts by weight of sodium saccharin; 0.5-1.5 parts by weight of peppermint powder flavoring 0.5-1.5 parts by weight of sodium lauryl sulfate; 0.7-0.9 parts by weight of sodium benzoate; 25-75 parts by weight of deionized water.